Evolutionary phylodynamics of foot-and-mouth disease virus serotypes O and A circulating in Vietnam. Issue 1 (December 2016) - Le, Van; Vu, Thi; Duong, Hong-Quan; Than, Van; Song, Daesub
Abstract Background Foot-and-mouth disease virus (FMDV) is one of the highest risk factors that affects the animal industry of the country. The virus causes production loss and high ratio mortality in young cloven-hoofed animals in Vietnam. The VP1 coding gene of 80 FMDV samples (66 samples of the serotype O and 14 samples of the serotype A) collected from endemic outbreaks during 2006–2014 were analyzed to investigate their phylogeny and genetic relationship with other available FMDVs globally. Results Phylogenetic analysis indicated that the serotype O strains were clustered into two distinct viral topotypes (the SEA and ME-SA), while the serotype A strains were all clustered into the genotype IX. Among the study strains, the amino acid sequence identities were shared at a level of 90.1–100, 92.9–100, and 92.8–100% for the topotypes SEA, ME-SA, and genotype IX, respectively. Substitutions leading to changes in the amino acid sequence, which are critical for the VP1 antigenic sites were also identified. Our results showed that the studied strains are most closely related to the recent FMDV isolates from Southeast Asian countries (Myanmar, Thailand, Cambodia, Malaysia, and Laos), but are distinct from the earlier FMDV isolates within the genotypes. Conclusions This study provides important evidence of recent movement of FMDVs serotype O and A into Vietnam within the last decade and their genetic accumulation to be closely related to strains causing FMD in surrounding countries.